Evaluation of Work Posture Using the REBA Method and Ergonomic Intervention at the Gelora Bakery MSME in Jakarta - Indra Rizki Pratama; Fredy Sumasto; Febriza Imansuri; Dianasanti Salati; B. Handoko Purwojatmiko (G-Tech: Jurnal Teknologi Terapan, 2026)
Micro, small, and medium enterprises (MSMEs) play a crucial role in community economic development, yet many neglect occupational safety and health (OSH) and ergonomic considerations for their workforce. An initial assessment at Gelora Bakery, a small-to-medium bakery enterprise in Jakarta, revealed significant ergonomic and safety deficiencies. Workers frequently engaged in unsafe manual handling tasks—bending awkwardly while lifting heavy loads such as flour sacks, baking material buckets, and butter containers without mechanical support. These unsafe working conditions pose a substantial risk of work-related musculoskeletal disorders (WMSDs) among workers. To address these concerns, this research employs the Rapid Entire Body Assessment (REBA), a standard ergonomic evaluation method, to systematically assess worker postures and quantify the risk of musculoskeletal injury. Based on the results of the REBA assessment, the highest score obtained was 10. This rating indicates a high-risk category and requires implementation of changes. This study formulates evidence-based recommendations for improving workplace safety and worker posture at Gelora Bakery. The implementation of ingredient storage shelves represents the primary intervention recommended to create a safer, healthier, and more efficient work environment.